The Prophet Isma'il (Ishmael) - Bakour Mohamad, Bachar (Nouresham Book Center, Al-Fatih Islamic nstitute, 2019)
Ishmael (Isma‘il) in Arabic or Hebrew means: 'God hears'61. He was Ibrahim’s (Abraham's) eldest son, born by Hagar (Hager). He was referred in eight Chapters in the Holy Qur’an, namely: Al-Baqarah [2: 125, 127, 133, 136, 140], Âl ‘Imran [3: 84], Al-Nisâ’ [4: 163], AlAn‘am [6: 86], Ibrahim [14: 39], Maryam [19: 54], Al-Anbiyâ’ [21: 85]. ......